Postcolonial Locations New Issues and Directions in Postcolonial Studies - Spencer, Robert; Valassopoulos, Anastasia 1973- (ROUTLEDGE, 2020)
Postcolonial Locations seeks to clarify the meaning of 'the postcolonial' through close textual readings, and prioritises material and located readings over more abstract theoretical discussions; it seeks to re-orient the field by providing practical explorations of what the discipline is for. The book begins with an introduction of the key theoretical debates in the field - between the universal and the particular; the global and the local - but it then goes on to demonstrate, via a series of close textual readings, that these distinctions are not always useful and that we can achieve a more comprehensive and complete reading of the multiple times, places and texts in which colonial power is both exerted and fought. An engaging and comprehensive guide to contemporary postcolonial studies, this book is essential reading for students as well as professors
Keywords: Postcolonialism; Literaturwissenschaft; Literaturtheorie; Postkoloniale Literatur; Postkolonialismus